2010
DOI: 10.1186/1742-4682-7-10
|View full text |Cite
|
Sign up to set email alerts
|

A thalamic reticular networking model of consciousness

Abstract: [Background]It is reasonable to consider the thalamus a primary candidate for the location of consciousness, given that the thalamus has been referred to as the gateway of nearly all sensory inputs to the corresponding cortical areas. Interestingly, in an early stage of brain development, communicative innervations between the dorsal thalamus and telencephalon must pass through the ventral thalamus, the major derivative of which is the thalamic reticular nucleus (TRN). The TRN occupies a striking control posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 118 publications
(127 reference statements)
3
64
0
2
Order By: Relevance
“…One could assume that the connectivity of the various thalamic nuclei may not change in a homogeneous manner under anesthesia. An important distinction between the roles of first-order and second-order relay nuclei (Guillery and Sherman, 2002), the reticular nucleus (Min, 2010), and the nonspecific intralaminar nuclei (Bogen, 1995;John, 2002) has been made with reference to consciousness. For example, the nonspecific thalamic system is involved in the regulation of cortical arousal and the higher integration of information ( Jasper, 1998a, b), and it is thought to enable consciousness.…”
Section: Hudetzmentioning
confidence: 99%
“…One could assume that the connectivity of the various thalamic nuclei may not change in a homogeneous manner under anesthesia. An important distinction between the roles of first-order and second-order relay nuclei (Guillery and Sherman, 2002), the reticular nucleus (Min, 2010), and the nonspecific intralaminar nuclei (Bogen, 1995;John, 2002) has been made with reference to consciousness. For example, the nonspecific thalamic system is involved in the regulation of cortical arousal and the higher integration of information ( Jasper, 1998a, b), and it is thought to enable consciousness.…”
Section: Hudetzmentioning
confidence: 99%
“…Previous studies have indicated that during discrete, consciously perceived events the thalamic γ activity matches the cortical γ activity, 47 and it has been suggested that the thalamus drives this coherence and thus enables cross-modal consciousness. 48 Rather than exerting unidirectional governance, the thalamus is thought to be a central node in complex cortico-thalamo-cortical loops. 46 The central recipient of cortical feedback is the caudate, which in turn back-projects to the thalamus.…”
Section: Reductions In Grey Matter Volume In Patients With Dpdmentioning
confidence: 99%
“…Schiff [41] captured this key role of the thalamus in arousal and consciousness disorders by proposing the notion of central thalamus for the anterior and posterior intralaminar nuclei plus paralaminar portions of related thalamic-associative dorsomedial, ventral anterior, ventral lateral and inferior pulvinar nuclei. The reticular thalamus, stratum and nucleus wrapping the thalamus should be involved in attention, the prerequisite to consciousness, filtering stimuli like a gateway to the cortex [42][43][44]. The case report by Sturm et al [16] supports this hypothesis.…”
Section: Dbs Targets To Alleviate Altered Arousal and Conscious Behavmentioning
confidence: 89%